Analysis of Factors That Play a Role in Enforcing Discipline of State Apparatus in Batam, Indonesia - Erniyanti, Erniyanti (HM Publisher, 2022)
Enforcement of state apparatus discipline in Indonesia is still a complex problem. In Batam, one of the largest industrial cities in Indonesia, the discipline of the state apparatus is an important factor in realizing good governance and improving public services. This research aims to analyze the factors that play a role in enforcing discipline among state officials in Batam. This research uses quantitative methods with a survey of 100 state officials in Batam. Data was collected through questionnaires and analyzed using factor analysis and multiple linear regression. The results of the research show that there are five factors that play a role in enforcing the discipline of state apparatus in Batam, namely: (1) leadership commitment, (2) firmness of rules, (3) awareness of state apparatus, (4) supervision system, and (5) strict sanctions. The factors of leadership commitment and firmness of rules have the most significant influence on enforcing the discipline of state officials in Batam. Leadership commitment and firmness of rules are the main keys to enforcing discipline in the state apparatus in Batam. Efforts are needed to increase leadership commitment and firmness of rules in enforcing discipline. Apart from that, efforts also need to be made to increase state officials’ awareness of the importance of discipline, strengthen the supervision system, and provide strict sanctions to state officials who violate discipline.